Geochemical Appraisal of Crude Oils from Umutu and Bomu Fields in the Niger Delta - Onojake; Chukunedum, Mudiaga; Leo, Osuji, Chigbu; Abrakasa (Bulletin of Earth Sciences of Thailand, 2021)
The geochemical appraisal of oils from the Umutu and Bomu fields in the Niger Delta reveals that the oils from the two fields bear an appreciable similarity considering their biomarker characteristics. The ternary plots for the % C27, C28 and C29 steranes indicates that the samples consist of mixed terrigenous and minor marine inputs. The Pr/nC17 vs the Ph/nC18 plot indicate that the oils are derived from type III kerogen, inferring that the sourcing organic matter were deposited in an dysoxic–oxic environment. The plot also infers that the Umutu samples are slightly biodegraded while the Bomu oils are not degraded. All samples in this study show near similar maturity level.